Ghrelin as an Anti-Sepsis Peptide: Review - Mathur, Nimisha; Mehdi, Syed F.; Anipindi, Manasa; Aziz, Monowar; Khan, Sawleha A.; Kondakindi, Hema; Lowell, Barbara; Wang, Ping; Roth, Jesse (Frontiers in Immunology, 2021)
Sepsis continues to produce widespread inflammation, illness, and death, prompting intensive research aimed at uncovering causes and therapies. In this article, we focus on ghrelin, an endogenous peptide with promise as a potent anti-inflammatory agent. Ghrelin was discovered, tracked and isolated from stomach cells based on its ability to stimulate release of growth hormone. It also stimulates appetite and is shown to be anti-inflammatory in a wide range of tissues. The anti-inflammatory effects mediated by ghrelin are a result of both the stimulation of anti-inflammatory processes and an inhibition of pro-inflammatory forces. Anti-inflammatory processes are promoted in a broad range of tissues including the hypothalamus and vagus nerve as well as in a broad range of immune cells. Aged rodents have reduced levels of growth hormone (GH) and diminished immune responses; ghrelin administration boosts GH levels and immune response. The anti-inflammatory functions of ghrelin, well displayed in preclinical animal models of sepsis, are just being charted in patients, with expectations that ghrelin and growth hormone might improve outcomes in patients with sepsis.